EFEKTIVITAS PERASAN DAUN MENIRAN (Phyllanthus niruri. L) SEBAGAI ANTIFUNGI TERHADAP PERTUMBUHAN JAMUR Candida albicans - Anggun Sophia Sophia; Suraini (Department of Biology, Faculty of Mathematics and Natural Sciences, Hasanuddin University, 2024)
Candida albicans is a normal flora in the healthy human body such as in the oral cavity, skin, digestive tract, reproductive tract and hair. Meniran plants contain flavonoid, tannin, saponin and alkaloid compounds that have antifungal effectiveness. The purpose of this study was to determine the effectiveness of meniran squeeze (Phyllanthus niruri. L) as an antifungal against the growth of Candida albicans. The type of research used is experimental research with a post test only control group research design. This research was conducted in February - July 2023 at the Biomedical Laboratory of Universitas Perintis Indonesia. The results showed the effectiveness of meniran leaf juice (Phyllanthus niruri. L) in inhibiting the growth of Candida albicans fungi where 40% concentration has an average diameter of the inhibition zone of 10.20 mm, 50% concentration has an average inhibition zone of 14 mm, 60% concentration has an average diameter of the inhibition zone of 19 mm, 80% concentration has an average inhibition zone of 22 mm. This shows that the higher the concentration, the greater the inhibition zone formed. In conclusion, meniran leaf juice (Phyllanthus niruri. L) has the ability to inhibit the growth of Candida albicans fungi.